Effects of dietary supplementation of Zn-nanoparticles on the growth performance and nutritional quality of Asian catfish, Clarias batrachus - Jewel, Abu Sayed; Haque, Ayenuddin; Akter, Nasrin; Akter, Sumaiya; Satter, Abdus; Sarker, Pallab Kumer; Marshall, David J.; Paray, Bilal Ahamad; Hossain, M. Belal (Frontiers in Sustainable Food Systems, 2024)
Nano-sized Zn particles are recognized for its ability to elevate fish health and well-being, enhancing antimicrobial and antioxidant capacities and reinforcing the immune system. In the present study we explored the effects of Zn-NPs supplementation on augmenting the growth performance and nutritional indicators and physiological aspects of the catfish, Clarias batrachus. Zn-NPs were prepared by heating the mixture of [Zn(CH3COO)2.2H2O], ethylene glycol and polymer surfactant (PVP) at 70°C for 45 min using an oil bath heater. The resultant solution was centrifuged at 6000 rpm on a heated plate at 70°C until the precipitation of Zn-NPs was achieved. Crystal structure, growth mechanisms and shapes of Zn-NPs were characterized by the atomic force microscopy. Produced Zn-NPs was characterized by spectrophotometer and the zeta potential and mean size was recorded as −32.5 ± 1.0 mV and 14.7 ± 2.5 nm, respectively. The experiment comprised six distinct test diets, categorized by the incorporation of Zn-NPs at levels of 0, 10, 20, 30, 40, and 50 mg/kg into the feed where the initial diet was employed as a control group, devoid of any Zn-NPs supplementation. Three glass aquariums were employed for each diet. In each aquarium, 12 fish with an initial mean weight of 5.23 ± 0.06 g were stocked. The fish underwent experimental feeding for 60 days, with the feed amount set at 3% of their body weight. After the experimental period, growth performance (weight gain, length gain, average daily gain, specific growth rate, thermal growth co-efficient, condition factor and survival rate), nutritional indices (feed conversion ratio, protein efficiency ratio, annual net protein utilization), proximate composition of muscle (protein, lipid, carbohydrate, ash and moisture), hematological parameters (RBC, WBC, hemoglobin, hematocrit, MCV, MCH, MCHC, total protein, albumin and globulin), serum lipid and enzymatic parameters (total cholesterol, HDL, LDL, triglycerides, ALP, AST, ALT, amylase, lipase and protease), and bioaccumulation of Zn in different organs of fish were estimated following standard methods. Growth analysis revealed that C. batrachus fed with Zn-NPs at 40 mg/kg of feed had significantly (p < 0.05) improved growth performance (WG = 18.87 ± 0.91 g, SGR = 2.52 ± 0.06% g/day, TGC = 1.09 ± 0.05 and CF = 1.47 ± 0.12), nutritional indices (FCR = 1.35 ± 0.06, PER = 2.24 ± 0.10 and ANPU = 41.46 ± 2.56%), hematological parameters, and enzymatic activity compared to control and other groups. The optimal dietary supplementation of Zn-NPs for final weight, weight gain and specific growth rate of C. batrachus was estimated to be ranged between 30.4 and 30.5 mg/kg per diet, respectively.